Blends of Thermoplastic Polyurethane and Polydimethylsiloxane Rubber: Assessment of Biocompatibility and Suture Holding Strength of Membranes - Rajan, Krishna Prasad; Al-Ghamdi, Ahmed; Parameswar, Ramesh; Nando, G. B. (International Journal of Biomaterials, 2013)
In the present investigation, a compatibilized blend of thermoplastic polyurethane (TPU) and polydimethylsiloxane (PDMS) is prepared by using copolymer of ethylene and methyl acrylate (EMA) as a reactive compatibilizer. Detailed in vitro biocompatibility studies were carried out for this compatibilized blend and the material was found noncytotoxic towards L929 mouse fibroblast subcutaneous connective tissue cell line. Microporosity was created on the surface of membranes prepared from the blend material by adopting the crazing mechanism. Cell proliferation and growth studies on the membranes surface showed that the microporous surface favoured ingrowth of the cells compared with a nonmicroporous surface. Suture holding strength studies indicate that the microporous membranes have enough strength to withstand the cutting and tearing forces through the suture hole. This blend material could be evaluated further to find its suitability in various implant applications.